MIXED PARASITIC INFECTION ON NATIVE MOUNTAIN GOATS ( BIG HORNE GOATS) OF DOHUK AREA - Al- bayati S. M; A. A; Al-nakshabandi (Basrah Journal of Veterinary Research)
Horne goat of the north mountains of Iraq (Kurdistan